PENINGKATAN EFESIENSI PROSES KERJA MELALUI METODE TIMES STUDY DAN PERBAIKAN TATA LETAK AREA PRODUKSI MELALUI METODE 5S STUDI KASUS UMKM PABRIK TAHU PAK RT - Tiara Wijaya; Muhammad Razif; Tuwandi Juniaro (Jurnal Liga Ilmu Serantau, 2026)
Soybeans are a major vegetable source widely consumed by Indonesians in processed forms such as tofu. The Pak RT Bukit Lama Tofu Factory in Palembang City is a home industry that produces tofu daily. However, operational activities in this factory still do not implement effective working time standards and efficient facility layout. This has the potential to cause low productivity and increase the risk of workplace accidents. This study aims to identify the actual conditions of the production process and working hours, evaluate efficiency using Time Study, and propose layout improvements based on ergonomic principles. In addition, the 5S method approach is applied to create a clean, orderly, and safe work environment. The results of this study are expected to provide a real contribution to improving work efficiency, workforce safety, and become a reference for developing better work systems in the small and medium industry sector.